HEAD OF HOUSEHOLD BEHAVIOR REGARDING THE ERADICATION OF DENGUE FEVER MOSQUITO NESTS IN LAMPAGEU VILLAGE, PEUKAN BADA SUBDISTRICT, ACEH BESAR REGENCY - Lensoni; Zahara, Hafni; Yanti, Susi; Zikra, Safaratul; Makhgirah, Nadilatul; Safira, Safra; Khatimah, Husnul; Indy, Elsa (Transpublika Publisher, 2023)
The